Uma olaria artesanal em uma comunidade ribeirinha no município de Abaetetuba/PA: relações possíveis com o ambiente e a escola - RODRIGUES, Francenilson Santos (2024)
The locus of this study is concretized in the relationship between nature and man through of your job. In the community of the Tucumanduba river, in the municipality of Abaetetuba/PA, where the riverside people live, for a long time the main guaranteeing the family's livelihood was through work in the brickyards. you were small factories that can be called artisanal, where clay (commonly clay) went through a process of industrial improvement giving rise to tiles and bricks widely used in construction. But over time this culture has lost space giving way to other ways of trades. However even in the days potteries are still responsible for generating sustenance for several families, in addition to keeping the history of a very knowledgeable people. so that they could concrete data can be collected while the importance and the real functional of the potteries, the study was no longer solely bibliographic and gave rise to two chapters of a practical nature, based on field research within the spaces of the potteries, as well as in schools, houses of residents, owners of potteries and workers. Quantitative and qualitative analyzes make up the technical path of methods and concepts obtained directly with the subjects of this relationship. As resident of the community and graduating from the natural sciences course, cast as essential steps for a good interpretation of the proposed theme, the understanding of that the riverside people, although far from urban reality, live daily with flawed and insufficient policies coming from the public power. although not yet enough, nature is the only place from which families can seek hope for a better future, and within this framework the pottery activity is just a reflection that can be added to a variety of other factors.